Using Flashcards to Increase EFL Students’ Vocabulary - Anggreani, Dwi Putri Toba; Rofiqoh, Rofiqoh; Nirwana, Nirwana; Thamrin, Nur Sehang (Journal of English Language and Education, 2025)
Flashcards are learning media in the form of double-sided cards that contain images and words. The objective of this research is to prove whether the use of flashcards can increase vocabulary of the seventh-grade students of SMPK GPID Sumbersari. This research used a quasi-experimental design involving two groups: experimental and control groups. The population consisted of two seventh grade classes. The data were collected through vocabulary test, which was administered twice as pre-test and post-test. Because the data were not normally distributed, the data were analyzed using the Mann- Whitney U test through SPSS version 24. The results showed that the difference between the post-test scores of the control and experimental classes differences significantly from 67 to 88. The Mann-Whitney test showed that both the experimental and control classes had a significant improvement (Z = -2.102, p = 0.036). It indicates that the research hypothesis is accepted. Thus, the use of flashcards can increase vocabulary of the seventh-grade students of SMPK GPID Sumbersari.